Thrips wedeliae (Priesner) (Thysanoptera: Thripidae) new to India: first description of the male - Tyagi, Kaomud; Kumar, Vikas; Pal, Shash (Zootaxa, 2024)
Thrips wedeliae (Priesner) was originally described based on a single female from Java, Indonesia. Recently, we have collected males and females of this species from Solanum mauritianum in Uttarakhand state, India. Here, males of T. wedeliae are diagnosed for the first time, along with the first record of this species from India. Due to the addition of this new record, the Indian species under the Thrips genus have increased up to 45 species. Detailed description, distribution, and illustrations of T. wedeliae are also provided.